Antibody response induced by the BNT162b2 mRNA COVID-19 vaccine in a cohort of health-care workers, with or without prior SARS-CoV-2 infection: a prospective study. (December 2021) - Buonfrate, Dora; Piubelli, Chiara; Gobbi, Federico; Martini, Davide; Bertoli, Giulia; Ursini, Tamara; Moro, Lucia; Ronzoni, Niccolò; Angheben, Andrea; Rodari, Paola; Cardellino, Chiara; Tamarozzi, Francesca; et al.
Abstract: Objectives: To assess the antibody response to BNT162b2 mRNA COVID-19 vaccine in a cohort of health-care workers (HCW), comparing individuals with previous severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and SARS-CoV-2-naive individuals. Methods: HCW were tested at T0 (day of first dose), T1 (day of second dose) and T2 (2–3 weeks after second dose) for IgG anti-nucleocapsid protein, IgM anti-spike protein and IgG anti-receptor binding domain (IgG-RBD-S). The antibody response was compared between four main groups: group A, individuals with previous infection and positive antibodies at baseline; group B, individuals with the same history but negative antibodies; group C, individuals with no infection history but positive antibodies; group D, naive individuals. Repeated measures analysis was used to compare results over time-points. Results: A total of 1935 HCW were included. Median IgG-RBD-S titre was significantly higher for group A (232 individuals) than for group B (56 individuals) both at T1 (A: 22 763 AU/mL, interquartile range (IQR) 14 222–37 204 AU/mL; B: 1373 AU/mL, IQR 783–3078 AU/mL, p 0.0003) and T2 (A: 30 765 AU/mL, IQR 19 841–42 813 AU/mL; B: 13 171 AU/mL, IQR 2324–22 688 AU/mL, p 0.0038) and for group D (1563 individuals; 796 AU/mL, IQR 379–1510 AU/mL at T1; 15 494 AU/mL, IQR 9122–23 916 AU/mL at T2, p < 0.0001 for both time-points). T1 values of group A were also significantly higher than T2 values of group D (p < 0.0001). Presence of symptoms, younger age and being female were associated with stronger antibody response. HCW infected in March showed a significantly stronger response (T1: 35 324 AU/mL, IQR 22 003–44 531 AU/mL; T2: 37 648 AU/mL, IQR 27 088–50 451 AU/mL) than those infected in November (T1: 18 499 AU/mL, IQR 11 492–27 283 AU/mL; T2: 23 210 AU/mL, IQR 18 074–36 086 AU/mL, p < 0.0001 for both time-points. Conclusions: Individuals with past SARS-CoV-2 infection had a strong antibody response after one single vaccine shot. A single dose might be sufficient for this group, regardless of the time elapsed since infection; however, the clinical correlation with antibody response needs to be studied.